2021
DOI: 10.1001/jamanetworkopen.2021.18811
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Insulin Resistance and Type 2 Diabetes With Gut Microbial Diversity

Abstract: IMPORTANCE Previous studies have indicated that gut microbiome may be associated with development of type 2 diabetes. However, these studies are limited by small sample size and insufficient for confounding. Furthermore, which specific taxa play a role in the development of type 2 diabetes remains unclear. OBJECTIVE To examine associations of gut microbiome composition with insulin resistance and type 2 diabetes in a large population-based setting controlling for various sociodemographic and lifestyle factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 26 publications
9
105
0
1
Order By: Relevance
“…In both diabetes and hyperlipidemia, Faith's PD values were lower than in those without these disorders. These findings recapitulate previous reports [44][45][46][47][48][49]. Whether these are causal links is not known.…”
Section: Discussionsupporting
confidence: 90%
“…In both diabetes and hyperlipidemia, Faith's PD values were lower than in those without these disorders. These findings recapitulate previous reports [44][45][46][47][48][49]. Whether these are causal links is not known.…”
Section: Discussionsupporting
confidence: 90%
“…A metagenome-wide association study (MGWAS) indicated that T2DM patients were accompanied by moderate degree of gut microbiome dysbiosis and the gut microbial markers might help classify T2DM (29). In addition, compared with participants without diabetes, patients with T2DM had a lower richness of gut microbiome (30). The mathematical model of the metagenomic profiles established based on the gut microbiome could identify T2DM with high accuracy (31).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber intake was also associated with less weight gain. Another study found that higher α diversity in the gut microbiome, along with more butyrate-producing species, were associated with a lower incidence of type 2 diabetes and lower rates of insulin resistance among non-diabetic individuals [48]. Therefore, we consider the increase in the Simpson diversity index observed with the test products in this in vitro model to be encouraging regarding their potential to impart beneficial effects on the human gut.…”
Section: Discussionmentioning
confidence: 75%